(untitled) (Research, Society and Development, 2020)
The new coronavirus pandemic disease (COVID-19) pandemic was first reported in Wuhan, China, in late 2019, and rapidly spread around the world. Considering its fast transmission rate, the new COVID-19 has become a threat to the public health worldwide. Thus, objective ideas based on scientific evidences must be proposed for the treatment of patients infected. Vitamin D is a hormone with important role in the regulation of the immune system functioning. The main sources of Vitamin D are food intake and synthesis process in the organism which starts in the skin through photoreaction with sun exposure. Then, the pre-Vitamin D is isomerized into pro-Vitamin D. Afterwards, it is metabolized in the liver into 25-hydroxivitamin D, and then converted into in the kidney into its active form, the 1.25-dihydroxivitamin D. Due to its pivotal role in the improvement of the immune response, Vitamin D can positively affect the treatment of several infecto-contagious diseases, such as influenza and H1N1. This concise review aims to inform about the use of Vitamin D as a possible ally in the treatment of COVID-19. The studies included in this review point out that Vitamin D can perform immunomodulatory and anti-inflammatory functions, which would significantly improve the treatment of viral infections. Further clinical trials and large populational studies should be carried out in order to better elucidate the effective role of Vitamin D in the treatment of patients with COVID-19.